DETEKSI DINI FAKTOR RISIKO PENYAKIT TIDAK MENULAR DI WILAYAH SUNGAI RAYA DALAM KABUPATEN KUBU RAYA - Ariyanti, Sri; Surtikanti; Erwhani, Indri (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
The increasing cases of Non-Communicable Diseases (PTM) will significantly add to the burden on the community and the government, because the handling requires no short time, large costs and high technology. PTM cases are not transmitted but are deadly and cause individuals to be less productive or less productive, but PTM can be prevented by controlling risk factors through early detection. In reducing the PTM case through controlling PTM risk factors in the community, it is necessary to have the same effort and understanding of the division of roles and support of the management of the PTM control program. In 2016, around 71 percent of the causes of death in the world were non-communicable diseases (PTM) which killed 36 million people per year. About 80 percent of these deaths occur in middle and low income countries. The purpose of this PPM activity is to conduct early detection and  PTM risk factors. Activities undertaken include checking blood pressure, some had increased blood sugar and cholesterol levels.The method of implementing the Community Service Program is checking vital signs and blood pressure, some had increased blood sugar and cholesterol levels. This activity was carried out during the PPSW Az Zahro Kubu Raya in Routin Meeting.